ANALYSIS OF CLINICAL CHARACTERISTICS OF NONMEDICAL USE OF TROPICAMIDE BY DRUG ADDICTS IN THE REPUBLIC OF KAZAKHSTAN - Prilutskaya, Mariya; Kuliev, Ramiz (European Scientific Journal, ESJ, 2015)
The article presents data on the issue of non-medical use of tropicamide in the Republic of Kazakhstan. The authors analysed the clinical characteristics of the polydrug abuse as a result of combined use of opioids and tropicamide by sampling drug addicts seeking narcological aid. Results indicate malignant state of substance addiction associated with the underlying opioid addiction. Currently the Republic of Kazakhstan faces a steady growth in chemical addictions as a result of increased circulation of traditional drugs and the emergence of new psychoactive substances. Since November 2013 the government has been actively focusing on the over-thecounter drug problem, taking a number of measures to restrict the distribution of psychotropic medications. Such medications include